2005
DOI: 10.1007/s10535-005-0009-6
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium-mediated transformation of Pisum sativum in vitro and in vivo

Abstract: Six pea (Pisum sativum L.) cultivars (Adept, Komet, Lantra, Olivín, Oskar, Tyrkys) were transformed via Agrobacterium tumefaciens strain EHA105 with pBIN19 plasmid carrying reporter uidA (β-glucuronidase, GUS, containing potato ST-LS1 intron) gene under the CaMV 35S promoter, and selectable marker gene nptII (neomycin phosphotransferase II) under the nos promoter. Two regeneration systems were used: continual shoot proliferation from axillary buds of cotyledonary node in vitro, and in vivo plant regeneration f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 52 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…We have also compared the explant source from garden-grown mature plants with those from in vitro seedling-derived plants in culture; the former were more responsive. For an efficient and reliable transformation system of pea, in vivo seedlings were reportedly preferable (Svábová et al 2005). Tiwari et al (2007) had shown higher transformation rates of mature leaves than younger leaves of Gentiana macrophylla.…”
Section: Discussionmentioning
confidence: 99%
“…We have also compared the explant source from garden-grown mature plants with those from in vitro seedling-derived plants in culture; the former were more responsive. For an efficient and reliable transformation system of pea, in vivo seedlings were reportedly preferable (Svábová et al 2005). Tiwari et al (2007) had shown higher transformation rates of mature leaves than younger leaves of Gentiana macrophylla.…”
Section: Discussionmentioning
confidence: 99%
“…Although pea is amenable to genetic transformation, this remains a challenge and precludes systematic characterization of gene function [234,235]. However, virus-induced gene silencing (VIGS) has become an important reverse genetics tool for functional genomics and VIGS vectors based on Pea early browning virus (PEBV, genus Tobravirus) are available for legume species and were successfully used to silence pea genes involved in symbiosis with nitrogen-fixing Rhizobium as well as development [236,237].…”
Section: Genomic Analysis Of Peamentioning
confidence: 99%
“…the so-called vacuum infiltration method), has been reported as an effective procedure to increase contact area between explant and Agrobacterium (Bechtold et al 1993). The vacuumassisted technique has been successfully applied in transformations of Arabidopsis thaliana (Clough and Bent 1998), Petunia hybrida (Tjokrokusumo et al 2000), Agapanthus (Suzuki et al 2001), wheat (Amoah et al 2001), Pinus radiata (Charity et al 2002), Brassica napus (Wang et al 2003), pea (Svabova et al 2005), and Coffea canephora (Kumar et al 2006). In addition, the successful regeneration of transformed plants, either directly from starting explants or indirectly from transformed callus, is an important step in plant genetic transformation.…”
Section: Introductionmentioning
confidence: 99%